Psychological Mechanisms for the Formation of Conflictological Culture in Students - Bakhtiyarovna, Khafizova Firuza (Indonesian Journal Publisher, 2025)
This study aims to explore the psychological mechanisms involved in the formation of a conflictological culture among university students. Utilizing a mixed-method approach, the research focuses on identifying key psychological traits, educational interventions, and environmental factors that contribute to students’ ability to manage and resolve conflicts constructively. Data were collected through validated psychometric instruments and semi-structured interviews involving a representative sample of students from Bukhara State University. The findings reveal that the development of empathy, emotional regulation, and reflective thinking plays a central role in building conflict resolution competencies. Furthermore, classroom-based training and mentoring programs were found to enhance students’ conflictological awareness and behavior. These results emphasize the importance of integrating psychological education into the university curriculum to foster a culture of peace and mutual understanding. The study contributes to the growing body of knowledge in educational psychology and offers practical recommendations for curriculum developers and educators.